Gifts, virtues and obligations of university volunteering - Puckering, Joanna, author.
1 online resource
Keywords: "This book takes a critical, grounded and ethnographic approach to elicit a deeper understanding of university volunteering. Anthropological theories of reciprocal gift exchange are used to re-visit some of the value-laden and at times conflicting ways of understanding volunteering as freely undertaken or coerced; altruistic or self-interested; and to explore how some of the changing uses and expectations of volunteering are related to the exercise of power and to the effect of social norms or structural constraints on agency. The book contains a detailed case study of a UK university, focusing on its relationships with local communities and voluntary organisations to illustrate the complex and culturally situated nature of volunteering and the gift. Joanna Puckering also draws on examples from countries such as the US and Australia to address wider questions of why people do what they do, and why volunteering motives and outcomes attract differing interpretations. This volume will be relevant to scholars from anthropology, sociology and geography as well as those involved in the higher education, voluntary, corporate, and social enterprise sectors"--